HOW TO MOTIVATE FASTER GROWTH IN COLOMBIA: THE LEADING SECTOR STRATEGY REVISITED (Artículo publicado en inglés) (Estudios Gerenciales, 2002)
This paper reproduces two public lectures given at an Incolda conference in Bogota, October 1, 2002 on «La Realidad de la Economía Colombiana ». It reviews the great structuralchanges in output and employment over recent decades and how macroeconomic policies can strengthen or weaken the natural forces underlying these changes. It distinguishes between potentially inflationary policies designed to increase demand ina monetary sense, and those that focus on institutional changes that enhance competition and mobility. It explains how inflation distorts the allocation of resources, and why it especially harms long-term housing finance and exports. It explains the logic of Lauchlin Currie¿s leading sector theory of growth and shows whyand how housing and exports can be given special protection to accelerate development.